Low Learning Achievements of Children in Elementary Schools of Tribal and Rural Pockets of Odisha What Do the Teachers Say? - Pradhan, Manoranjan (JOURNAL OF INDIAN EDUCATION, 2015)
According to several surveys and reports (mainly Annual Status of Education Report), the learning achievements of the students at elementary stage in government schools of rural and tribal Odisha is not satisfactory in comparison to their counterpart private schools. Instead of all efforts made by administration in terms of incentives and interventions, the learning achievement is not up to satisfaction. The study is based on the status of the performance of learners in different subjects according to the ASER 2014. An attempt made to know the factors accountable for the gloomy picture of elementary school students in tribal dominated and rural pockets of Odisha. The opinions of 151 experienced teachers working in these areas from 39 Blocks (4 major tribal districts) were taken into consideration. For data collection, 34 questions were asked to teachers related to the issues on infrastructure, teachers, students, pedagogy, community involvement and administrative matters. The suggestive measures to improve the performance of the learners were also reflected in the present study.